Anniversary Feature Papers - Liang, Steven (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The Journal of Manufacturing and Materials Processing (JMMP) aims to provide an international forum for the documentation and dissemination of recent, original, and significant research studies in the analysis of processes, equipment, systems, and materials related to material heat treatment, solidification, deformation, addition, removal, welding, and accretion for the industrial fabrication and production of parts, components, and products. The JMMP was established in 2017 and has published more than 300 contributions. It has been listed in the ESCI, Inspec (IET), and Scopus (Elsevier). In celebration of the anniversary of the JMMP, the Editorial Office has put together this Special Issue, which includes several representative papers that reflect the vibrant growth and dynamic trend of research in this field.